The Factors Affecting Customer Repurchase Intention of Economic Hotels in Kunming - Hu, Jinrui; Run, Pharatt (Proceedings of International Conference of Graduate School on Sustainability, 2024)
This research studies the influence of demographics, marketing mix (7Ps), and sustainability on customer repurchase intentions at an economic hotel in Kunming. The researcher used the questionnaire as the research tool and collected data from sample customers who had stayed at the Economic Hotel in Kunming. The data was analyzed using statistical techniques, including T-tests, one-way ANOVAs, and multiple linear regression analyses to test the influence of demographics, marketing mix (7Ps), and sustainability on customer repurchase intentions. The first hypothesis was tested, and the results found that the differences in education, occupation, and income significantly affected different repurchase intentions of economic hotels. For the second hypothesis tested, the results found that physical evidence, process, price, and people (staff) significantly influence customer repurchase intention. For the last hypothesis tested, the results also found that efficiency, planet, and people (sustainability) significantly influence customer repurchase intention. The results show that demographics, marketing mix (7Ps), and sustainability have influenced customer repurchase intentions in the economic hotel industry. This research provides valuable insights into the economic hotels, other stakeholders, and especially top managers who can use these results to apply their marketing strategies to increase customer repurchase intentions in Kunming or other provinces in China.